The biosynthesis of adrenal C 11-oxy C21 steroids, implicated in 21-hydroxylase deficiency-21-desoxycortisol and 21 desoxycortisone and their downstream metabolism - Barnard, Lise (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.